The FMEA methodology applied in the design of the Powertrain assembly of a Baja SAE vehicle - Pereira, Gabriel Rodrigues; Baldissera, Alisson; Roque, Cassiano Basaglia; Menezes, Miguel Ângelo (Seven Editora, 2023)
The Baja SAE Project is a university engineering challenge, which proposes the construction of an off-road vehicle and its application in competitions with challenging dynamic tests. Each year these competitions become increasingly difficult and, with this, issues such as the breakage and maintenance of components of these vehicles appear. These problems affect the Powertrain sector of the TEC-Ilha Baja SAE Team that sought to use methods and tools to solve these issues, such as FMEA. This methodology is defined by the NBR 5462 standard of ABNT and consists of recording the useful life of the components used and analyzing the failures that occurred in these components in a period, seeking to evaluate three basic points, which are the severity, occurrence and detection. That said, after prospecting all the episodes of breakage of vehicle components in the last 10 years of competitions, the Team elaborated, according to this method, the decision matrices linked to the three basic pillars, in order to establish relationships and scores for each case and so that it was possible to calculate the Risk Priority Number, the NPR, directing attention during vehicle maintenance and repairs. In all, 12 failures were detected in components connected to the transmission, which were classified according to their NPR. Although there is an ideal condition that establishes that the correction of all failure modes provides better operation of the vehicle, only the most critical failure modes are selected, due to the cost associated with maintenance. By observing the NPR of each failure it is possible to conclude that the engine components are the ones that suffer most from the challenges imposed on the vehicle, having the displacement of the ignition coil, the fracture of the crankshaft and the compromise of the carburetor as the most critical points, which have NPR’s of 360, 280 and 252, respectively, and the less critical CVT and reduction box components with NPR’s ranging from 10 to 90. Thus, the application of the FMEA methodology in the project of the TEC-Ilha Baja SAE Team provides an effective and systematized analysis of the failure modes that are inherent to the components of the vehicle’s power transmission subsystem, serving as a basis for decision-making in the scope of programming and carrying out preventive maintenance of the most critical components. DOI:https://doi.org/10.56238/alookdevelopv1-170